2012
DOI: 10.1620/tjem.227.289
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Exercise as a Key Determinant of Improvement in Insulin Sensitivity in Type 2 Diabetes Patients

Abstract: Exercise duration and intensity are important parameters in exercise prescription and play a major role in improving insulin sensitivity (including transient and persistent improvement effects following cessation of training) in patients with type 2 diabetes mellitus (T2DM). However, whether duration or intensity of exercise is the more important factor has yet to be established. Therefore, we aimed to determine whether exercise prescriptions differing in duration and intensity differ in their ability to aid T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…Obtained results showed that our training program has positively influenced glucose uptake and insulin action. Our study results are in accordance with another study result's conducted by Jing Li and colleagues [18]. In their study titled "Duration of exercise as a key determinant of improvement in insulin sensitivity in type 2 diabetes", they observed an increased glucose uptake and insulin action improvement even 15 days after exercise training cessation.…”
Section: Study Limitationsupporting
confidence: 92%
“…Obtained results showed that our training program has positively influenced glucose uptake and insulin action. Our study results are in accordance with another study result's conducted by Jing Li and colleagues [18]. In their study titled "Duration of exercise as a key determinant of improvement in insulin sensitivity in type 2 diabetes", they observed an increased glucose uptake and insulin action improvement even 15 days after exercise training cessation.…”
Section: Study Limitationsupporting
confidence: 92%
“…In one report, a greater and more persistent training effect was observed in individuals in a low volume/moderate intensity exercise training group compared to individuals in a low volume/vigorous intensity group (33). Other studies have reported that duration of exercise is also critical in determining the magnitude of the training effect regardless of volume or intensity (42,78). Furthermore, recent evidence demonstrated that the type-and not duration-of exercise was the key to improvements in HbA1c levels in individuals with T2D (34).…”
Section: Physiological and Metabolic Adaptations To Exercisementioning
confidence: 97%
“…Physical activity is one of the three cornerstone recommendations (along with diet and medication) in the treatment of type 2 diabetes . Exercise training improves aerobic capacity and muscular strength and is often associated with fat loss and increased muscle mass.…”
Section: Introductionmentioning
confidence: 99%